An energy-efficient enhanced virtual resource provision middleware in clouds. (1st January 2014) - Liu, Dongbo
In the past few years, cloud computing has emerged as a promising paradigm for delivering IT-infrastructures, platforms, applications and services. The consolidation of this new paradigm in both commercial business and academic research requires that the underlying resources should be economically managed. In this paper, we present a resource provision framework, which is aiming at improving the energy-efficiency of cloud-based data centres. The proposed framework is implemented as a lightweight middleware, which consists of three novel services that enable cloud providers to up/down scale their virtual resource pool in an efficient manner. Extensive experiments are conducted to evaluate the effectiveness and the performance of the proposed middleware in real-world cloud platform. The results indicate that it can significantly improving the energy-efficiency in virtualised clouds without significantly degradation on application performance.